2007
DOI: 10.1016/j.ejheart.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A change in N‐terminal pro‐brain natriuretic peptide is predictive of outcome in patients with advanced heart failure

Abstract: Background: The prognosis of chronic heart failure has improved with modern medical therapy. However, identifying those patients who fail to respond to such therapy and therefore those who remain at high risk is notoriously difficult. The B-type natriuretic peptides are established independent predictors of prognosis in CHF. However, the relevance of a change in NT-proBNP concentration over time in advanced heart failure is unknown. Methods: We prospectively studied 133 patients with advanced CHF referred for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
3
19
0
2
Order By: Relevance
“…We have previously shown that stratification of patients into 4 categories according to BNP levels at 2 time points with respect to a median concentration provided prognostic information in patients with chronic HF beyond that of a single determination (3). The same approach and conclusion can be found in a prospective study that enrolled 133 patients with severe HF referred for consideration of cardiac transplantation (18). In the present study, the threshold level was derived from an ROC analysis and the calculated optimal cutoff concentration (1,078 pg/ml) is in fact close to the median concentration at study entry (861 pg/ml), so that our findings should be relatively independent of the way the threshold was calculated.…”
Section: Figure 3 Kaplan-meier Curves For All-cause Mortality In the mentioning
confidence: 60%
“…We have previously shown that stratification of patients into 4 categories according to BNP levels at 2 time points with respect to a median concentration provided prognostic information in patients with chronic HF beyond that of a single determination (3). The same approach and conclusion can be found in a prospective study that enrolled 133 patients with severe HF referred for consideration of cardiac transplantation (18). In the present study, the threshold level was derived from an ROC analysis and the calculated optimal cutoff concentration (1,078 pg/ml) is in fact close to the median concentration at study entry (861 pg/ml), so that our findings should be relatively independent of the way the threshold was calculated.…”
Section: Figure 3 Kaplan-meier Curves For All-cause Mortality In the mentioning
confidence: 60%
“…In patients with advanced heart failure referred for consideration of cardiac transplantation, NT-proBNP (or a change in NT-proBNP) was the only independent predictor of all-cause mortality or need for transplantation and out-performed conventional prognostic indicators including left ventricular ejection fraction (LVEF), peak maximum oxygen uptake, Heart Failure Survival Score and plasma neurohormones [49][50][51]. The selection of patients for such expensive and finite resources is difficult.…”
Section: Guide To Prognosismentioning
confidence: 99%
“…Changes in either BNP or NTproBNP over brief periods are related to subsequent outcomes in both acute coronary syndromes and acute decompensated heart failure (HF) (1,2). Changes in NT-proBNP over months predict outcome in advanced HF (3). The relationship between changes in peptide levels over longer intervals with outcomes in a large group with stable CHF has been explored for BNP (4) but not NT-proBNP.…”
mentioning
confidence: 99%